2011
DOI: 10.1088/0953-4075/44/5/055206
|View full text |Cite
|
Sign up to set email alerts
|

Ionization and ionic fragmentation of tetrahydrofuran molecules by electron collisions

Abstract: Electron impact ionization and ionic fragmentation of tetrahydrofuran molecules in the gas phase were studied in the energy range from ionization threshold up to 150 eV using the technique of mass spectrometry. The cation mass spectra, ionization and ionic fragmentation efficiencies were measured over this energy range. Well-resolved mass peaks were detected in the mass range 10-72 amu and assigned to corresponding ionic molecular fragments. The most abundant cation in the mass spectra is at 42 amu. Appearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 37 publications
4
40
1
Order By: Relevance
“…The results of Champion [17] are, however, shifted towards lower energies and have a higher peak value compared to all the other data presented here. Dampc et al [15] have reported scaled total ionisation cross section data using a mass spectrometry method and their data are higher than all the results except those of Champion [17]. For additional comparison total ionisation cross sections calculated using the BEB method [34] are shown.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The results of Champion [17] are, however, shifted towards lower energies and have a higher peak value compared to all the other data presented here. Dampc et al [15] have reported scaled total ionisation cross section data using a mass spectrometry method and their data are higher than all the results except those of Champion [17]. For additional comparison total ionisation cross sections calculated using the BEB method [34] are shown.…”
Section: Resultsmentioning
confidence: 93%
“…Much of this work is dedicated to the study of electron transport and reactivity in biological media, including vibrational and electronic excitation, dissociative attachment, electron trapping and reactivity in condensed THF along with the report of measurements of elastic and total scattering cross sections [14]. Electron-impact ionisation for THF has been studied experimentally by two groups [15,16] and theoretically by two groups [17,18]. The theoretical total inelastic cross section data for THF is reported by Fuss et al [16] and Baek et al [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Masses in the range 46-62 amu have been reported for electron impact with low abundance below 0.6% relative intensities [25] which are not resolved here. To emphasize the main fragments, the following cations are not displayed in Figure 3: the hydrogen (1 amu) peak is suppressed due to poor transmission of fast light ions; a peak at 4 amu stems from the helium carrier gas, peaks larger than 73 amu from small pyrimidine or TMP contamination.…”
Section: Tetrahydrofuranmentioning
confidence: 66%
“…Thus, we compare our data to spectra for electron collisions with electron impact above all appearance energies. The most notable discrepancy among mass spectra for electron collisions was the appearance of mass peak around 55 amu, that was reported by Fuss [33] and Ren [30], but could not be observed by Gallegos [23], Collin [24], Dampc [25], the massbank.jp [26] and NIST [27]. The formation of that mass peak requires the simultaneous breakage of two C-O bonds, which is energetically unfavorable [31].…”
Section: The Parent C 4 H 8 Omentioning
confidence: 91%